The influence of teaching films upon the children of underschool age - Tidikienė , Z. (Psichologija, 1972)
Our investigations have shown that the use of teaching screen, when introducing children of 5-7 years old to the surroundings, perfects the process of teaching to the utmost and at the same time develops the personality of a preschool child. Teaching films help the children to master concrete, generalized, expanded and systematized knowledge. Pedagogically aimed presenting of cognitive material in a film forms the child’s attitude towards social phenomena, gives him some ways of generalized analysis. The emotionality of screen images stimulates the child’s speech activity and the texts act upon his fluency, expressiveness, picturesqueness.
Keywords: teaching films; underschool age